Hubungan Dukungan Keluarga Dengan Pemberian Kolostrum Pada Bayi Di Wilayah Kelurahan Pakansari Kecamatan Cibinong Kabupaten Bogor Tahun 2021 - Fungki Claudia Pahlevi (Jurnal Kesehatan Rajawali, 2021)
ABSTRACT Relationship between Family Support and Giving Colostrum to Babies in the Independent Practice of Midwives in the Pakansari Village, Cibinong District, Bogor Regency in 2021 Pahlevi F.C, Kusmiran E, Mulyani I Background: Colostrum is the first milk that comes out after the birth of a baby. Colostrum has a good content for babies, one of which is an immune substance that can protect babies from disease. There is a lot of debate about giving colostrum circulating in the community. Therefore, in this stage of breastfeeding, breastfeeding mothers need the role of the family to support the provision of colostrum and ensure that colostrum is good for their babies. Research Purpose: This study aims to see the relationship between family support and giving colostrum to infants. This research was conducted in the Independent Practice of Midwives in Pakansari Village, Cibinong District, Bogor Regency in 2021. Research Method: This research is a quantitative analytic survey using a Cross Sectional approach design and using primary data. The population in this study were mothers who gave birth in the Midwife Independent Practice in the Pakansari Village, Cibinong District, Bogor Regency, which amounted to 32 people, the number of samples was 32 respondents. Data collection was done by using total sampling technique. Results: The results showed that the highest percentage was those who had poor support as many as 17 (53.1%) respondents, and 17 (53.1%) respondents who did not give colostrum. The results of the chi-square test obtained p-value < 0.001 (α < 0.05). Conclusion: There is a relationship between family support and giving colostrum to babies in the Independent Practice of Midwives in the Pakansari Village, Cibinong District, Bogor Regency in 2021. Keywords: Family Support, Giving Colostrum